ANALISIS KESALAHAN BERBAHASA DALAM RUBRIK â€œFOKUSâ€ MAJALAH PENDAPA TAMANSISWA - Yosephus Dominikus Fernandez; Mukhlish Mukhlish (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aims to describe linguistics error on â€œFokusâ€ rubric of Pendapa Tamansiswa magazine. The errors identified are 1) spelling errors, 2) morphologic errors 3) syntactic errors 4) and lexicon errors. This is a qualitative descriptive research which focuses on sentences containing linguistics errors. The data are gathered from sixteen packs of rubric â€œFokusâ€ in Pendapa Tamansiswa magazine in eight bundle of publishing by using free intensive reading and noteÂ taking techniques. The data were analyzed by using evenly distributed methods with direct-substance-distribution techniques, substituting techniques, disappearing techniques, extension techniques, and reversing techniques. The result showed that (1) there are 133 error sentences or 11,24% contain of error in letter using, dictions, punctuation, and spelling. (2) There are 8 sentences with morphologic errors or 0,68% which contain affixes and reduplications errors. (3) There are 70 syntactic errors in 70 sentences or 5,91% which contain sentence patterns errors and word choise of